2017
DOI: 10.1016/j.jaip.2017.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Anaphylaxis: Mortality Rate and Risk Factors

Abstract: Up to 5% of the US population has suffered anaphylaxis. Fatal outcome is rare, such that even for people with known venom or food allergy, fatal anaphylaxis constitutes less than 1% of total mortality risk. The incidence of fatal anaphylaxis has not increased in line with hospital admissions for anaphylaxis. Fatal drug anaphylaxis may be increasing, but rates of fatal anaphylaxis to venom and food are stable. Risk factors for fatal anaphylaxis vary according to cause. For fatal drug anaphylaxis, previous cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
291
3
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 417 publications
(312 citation statements)
references
References 74 publications
8
291
3
10
Order By: Relevance
“…A very high rate of challenge‐proven food allergy was described with 10.4% of participating children allergic to egg, peanut or sesame . Although rates of anaphylaxis to foods are increasing, those of fatal anaphylaxis appear to be stable in most countries . However, Australia reported a significant increase, of 9.7% per year, in fatal food anaphylaxis between 1997 and 2013 .…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…A very high rate of challenge‐proven food allergy was described with 10.4% of participating children allergic to egg, peanut or sesame . Although rates of anaphylaxis to foods are increasing, those of fatal anaphylaxis appear to be stable in most countries . However, Australia reported a significant increase, of 9.7% per year, in fatal food anaphylaxis between 1997 and 2013 .…”
Section: Introductionmentioning
confidence: 74%
“…Food‐induced anaphylaxis occurs most commonly in young children, with peanut being the commonest cause worldwide, along with tree nuts, cow's milk and egg . Fatal food anaphylaxis is reported to account for 0.03–0.3 deaths per million inhabitants yearly worldwide, with peanut being the leading causative allergen, peanut, along with tree nuts, account for 55–87% cases of fatal food anaphylaxis . Most fatal food‐induced reactions occur in adolescents and young adults most likely due to increased risk taking behaviours in this age group, although a possible physiological predisposition to more severe reactions in this age group cannot be excluded .…”
Section: Clinical Manifestations Of Peanut Allergymentioning
confidence: 99%
See 2 more Smart Citations
“…Pre‐existing pulmonary disease including asthma was identified as a risk factor for hypoxemic reactions and delayed deterioration of anaphylaxis in general, and to specifically impair the outcome of food‐induced anaphylaxis . Some authors accordingly observed an increased incidence of respiratory symptoms during sting‐induced anaphylactic reactions in a subgroup of atopic patients which was likely to contain a significant proportion of individuals with concurrent asthma .…”
Section: Long‐term Risk Factorsmentioning
confidence: 99%